Effect of long-lasting nutritional prehabilitation on postoperative outcome in elective surgery for IBD. Issue 3 (March 2021) - Fiorindi, Camilla; Cuffaro, Francesca; Piemonte, Guya; Cricchio, Marta; Addasi, Rami; Dragoni, Gabriele; Scaringi, Stefano; Nannoni, Anita; Ficari, Ferdinando; Giudici, Francesco
Summary: Background & aims: Preoperative patient care optimisation appears to be crucial for obtaining good surgical outcomes. Enhanced Recovery After Surgery (ERAS) underlines the necessity to recognize and treat malnutrition perioperatively and to prehabilitate with interventions that can modulate the lean body mass before and after surgery. This procedure has been extensively reported in colorectal cancer patients but in Inflammatory Bowel Disease (IBD) it has not yet been clearly evaluated. The aim of this study was to implement the perioperative nutritional items in surgical Crohn's disease (CD) and ulcerative colitis (UC) patients electively operated in an ERAS setting, thus to clarify the impact of a long-lasting prehabilitation program in IBD. Methods: Consecutive adult patients (age ≥18) were included as soon as scheduled for elective surgery for CD or UC. The nutritional intervention included personalized dietary counseling and oral nutritional supplements when necessary. Data prospectively recorded in each phase were: FFM, FM, FFMI and phase angle detected with BIVA, weight, BMI, unintended weight loss, DASI, energy and nutritional intake, gastrointestinal symptoms and bowel functions. Nutritional risk was detected according to the NRS 2002 screening tool. The impact of early oral nutrition on postoperative recovery was analysed. Results: A total of 61 IBD patients (45 CD and 16 UC) were included. Muscle wasting was present at baseline assessment in 28% of cases, significantly associated with the presence of ileostomy (p < 0.011) and of a previous IBD surgery (p < 0.011). During the preoperative phase, there was a significant improvement in weight, BMI, FFM (CD p = 0.035; UC p = 0.017), FFMI (CD ns; UC p = 0.011) and phase angle (CD p = 0.014; UC p = 0.027). During the intra-hospital phase, weight and FFM decreased due to the catabolic effect of surgery, but in the whole perioperative period, both CD and UC patients did not change significantly in terms of body composition. Patients with earlier resumption of oral feeding had a significantly shorter hospital stay and a faster recovery of bowel function with no significant relationship with early postoperative complications. Conclusions: Nutritional prehabilitation positively modulated the body composition of IBD patients scheduled for elective surgery and therefore could represent a beneficial strategy to attenuate the impact of the surgical stress response on lean tissue in an ERAS setting. This effect is even more evident in high nutritional risk patients. Early postoperative oral feeding seems feasible and well tolerated in IBD. This approach positively influences the restoration of bowel function and the duration of hospital stay.